Exploring the Accounting Teaching Practices of Lecturers in a Higher Education Institution: A Case at a South African University - Grate Ndabezihle Moyo; Boitumelo Moreeng; Moeketsi Mosia (Social Sciences, Humanities and Education Journal (SHE Journal), 2023)
This paper aimed to determine the accounting lecturers’ teaching practices at a South African university. Teaching practices are a complex set of ways that lecturers use for instruction. When compromisingly crafted/implemented, they impact on success. In accounting education, teaching practices were found cognitively driven to determine success. Cognitivism learning theory guided the study. It emphasises mental processes, thinking, solving complex problems, and focusing on tasks requiring increased information processing, and procedural rules. The related elements enhance accounting teaching practices. This paper used a qualitative exploratory research methodology, enabling the researcher’s engagement with participants in their natural settings. Participants were purposefully selected for this study. Data was generated through individual semi-structured interviews to determine accounting lecturers’ practices. Issues including participants’ teaching practices and challenges experienced were explored. Data was thematically analysed. Findings suggest that current accounting teaching practices are detriment to performance. Hence this paper suggests that teaching practices require intervention